Implementation of the Literacy Program at the 006 Bangsal Aceh Public Elementary School, Dumai City - Nelsy, Asma; Mahdum, Mahdum; Saam, Zulfan (FKIP-Universitas Riau, 2022)
The development of education and culture is directed at improving the quality of life of Indonesian people, increasing productivity and competitiveness, revolutionizing the nation's character, as well as strengthening diversity and strengthening Indonesia's social restoration. The State Elementary School 006 Bangsal Aceh takes part in the government program, namely the National Literacy Movement. In response to this, the researchers observed for approximately five years the iteration program at this school was running. This study aims to describe (1 How is the implementation of the literacy program, (2) What are the obstacles and solutions that are carried out in the Implementation of the literacy program, (3) How is the relationship between students' reading interest and the implementation of the literacy program, and (4) How is the relationship between students' interest in writing for students with the implementation of literacy programs at SD Negeri 006 Bangsal Aceh Dumai. This study uses a qualitative approach with a descriptive type. Sources of research data are the principal, 5 teachers, and 4 students. Data collection techniques using the Miles and Huberman models are data reduction, data display, and drawing conclusions. Test the validity of the data using technical triangulation and source triangulation. The results of the study indicate that (1) the implementation of the program has not been realized properly, (2) the obstacles to implementing the program are a less supportive environment, incomplete infrastructure, unliterate parents, and lack of examples of teachers in literacy habituation in schools (3) students' reading interest is still low, (4) students' writing interest is still low.